Almost periodic distributions and crystalline measures - S. Yu. Favorov (Математичні Студії, 2024)
We study temperate distributions and measures with discrete support in Euclidean space and their Fourier transforms with special attention to almost periodic distributions. In particular, we prove that if distances between points of the support of a measure do not quickly approach 0 at infinity, then this measure is a Fourier quasicrystal (Theorem 1).